The Importance of Introduction to the Basics of Islam from an Early Age (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The introduction of the basics of Islam from an early age is something that is important because the age of a child is very crucial or something that really needs attention in building and educating the character of the child. Early childhood learning and experiences are things that will stick in the minds of children and affect a little or a lot during their adolescence and adulthood. The purpose of introducing the basics of religion is to instill the foundation of Islam in children's lives and hope that they will become human beings who have a good and good Islamic spirit. The method that will be used is to ask questions and give rewards and punishments. Because children from an early age curiosity must use a reward or punishment, something simple, and the punishment is light. This follows the inclination of children's nature. The importance of introducing Islam from an early age is because it is to help children become good and good Muslims according to Allah SWT, the Rasulullah, the Ulama.